Heating and evaporation of suspended water droplets: Experimental studies and modelling - Strizhak P. A. Pavel Alexandrovich; Volkov R. S. Roman Sergeevich; Castanet G. Guillaume; Lemoine F. Fabrice; Rybdylova O. Oyuna; Sazhin S. S. Sergey Stepanovich (2018, 2018)
Title screen